Tranformasi Strategi Pembelajaran PAI di PTKIN Berbasis Model Pembelajaran Problem Based Learning - Eko Purnomo; Ashif Az Zafi; Lalu Abdurrahman Wahid (FONDATIA, 2022)
Islamic religious education learning, especially the material delivered from the lower level to the upper and advanced levels, has a different emphasis on weight. Without being accompanied by methods and strategies that are well packaged by the teacher, which are adapted to the circumstances of the students, it has the effect of a lack of understanding, less interest and motivation from students. PAI Learning Strategy with Problem Based Learning model or Problem Based Learning (PBM) is a learning method that teaches students to solve problems and reflect on their experiences, making it possible to grow and develop thinking skills with reasoning, communicative, and connections in problem solving that has meaning. , relevant and contextual. The purpose of this study is to describe the effectiveness of problem based learning strategies through methods, procedures and strategies in developing Islamic Religious Education learning at PTKIN. This research is a qualitative research with library research. The results of this study indicate that the Problem Based Learning learning model is relevant in its application to the PAI Learning Strategy so that it can be collaborated with other conventional models in order to achieve optimal learning outcomes. The Problem Based Learning model makes it easier for students to understand and connect their knowledge to the reality of contextual problems in the midst of people's lives.